2015
DOI: 10.1152/jn.00601.2013
|View full text |Cite
|
Sign up to set email alerts
|

High-conductance states and A-type K+ channels are potential regulators of the conductance-current balance triggered by HCN channels

Abstract: An increase in the hyperpolarization-activated cyclic nucleotide-gated (HCN) channel conductance reduces input resistance, whereas the consequent increase in the inward h current depolarizes the membrane. This results in a delicate and unique conductance-current balance triggered by the expression of HCN channels. In this study, we employ experimentally constrained, morphologically realistic, conductance-based models of hippocampal neurons to explore certain aspects of this conductance-current balance. First, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 116 publications
(174 reference statements)
3
39
0
Order By: Relevance
“…For instance, computational investigations using multi-compartment models have suggested that, in CA1 pyramidal neurons, interactions between h-channels and TASK-like potassium leak channels could explain paradoxical findings such as membrane depolarization after h-channel block (Migliore and Migliore, 2012). Other modelling work with CA1 pyramidal neurons has predicted that A-type potassium channels modulate the efficacy of the h-current balance between conductance and current, which exhibit counteracting effects of decreasing input resistance and depolarizing the membrane potential, respectively (Mishra and Narayanan, 2015). It is thus reasonable to also consider dendritic functional maps for different inhibitory cell types, and specifically O-LM cells which, to our knowledge, has not been done to date.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, computational investigations using multi-compartment models have suggested that, in CA1 pyramidal neurons, interactions between h-channels and TASK-like potassium leak channels could explain paradoxical findings such as membrane depolarization after h-channel block (Migliore and Migliore, 2012). Other modelling work with CA1 pyramidal neurons has predicted that A-type potassium channels modulate the efficacy of the h-current balance between conductance and current, which exhibit counteracting effects of decreasing input resistance and depolarizing the membrane potential, respectively (Mishra and Narayanan, 2015). It is thus reasonable to also consider dendritic functional maps for different inhibitory cell types, and specifically O-LM cells which, to our knowledge, has not been done to date.…”
Section: Discussionmentioning
confidence: 99%
“…S1 A-C). Because of the domination of the underlying rhythmic high-conductance state (36), the LFP amplitudes across recording sites were not significantly different with the insertion of HCN channels. However, the incorporation of HCN channels introduced a significant location-dependent phase lead in the LFPs across all recording sites, when compared with corresponding LFPs computed in the absence of HCN channels ( Fig.…”
Section: Significancementioning
confidence: 95%
“…2-3). First, there is significant degeneracy in the emergence of neurophysiological properties, where disparate combinations of channels could come together to elicit similar functional properties Narayanan, 2014, 2015;Drion et al, 2015;Foster et al, 1993;Gjorgjieva et al, 2016;Goldman et al, 2001;Grashow et al, 2010;Marder, 2011;Marder and Goaillard, 2006;Marder and Taylor, 2011;Mishra and Narayanan, 2015;Rathour et al, 2016;Narayanan, 2012a, b, 2014;Taylor et al, 2009). Second, the dependence of different physiological properties on distinct peer-reviewed) is the author/funder.…”
Section: Degeneracy In Neuronal Physiological Propertiesmentioning
confidence: 99%
“…16, 2017; in regulating intrinsic properties and their location-dependent characteristics, especially in electrotonically non-compact hippocampal pyramidal neurons (Dhupia et al, 2015;Golding et al, 2005;Krichmar et al, 2002;Mainen and Sejnowski, 1996;Narayanan and Chattarji, 2010;Spruston et al, 1994;Spruston et al, 1993), and could significantly contribute to degeneracy in the emergence of single-neuron physiology. Finally, depending on the localization profiles and voltage-dependent properties of different channels they may or may not spatiotemporally interact (Migliore and Migliore, 2012;Mishra and Narayanan, 2015;Rathour and Narayanan, 2012b).…”
Section: Degeneracy In Neuronal Physiological Propertiesmentioning
confidence: 99%